Creating a learning society (Dimensión Empresarial, 2017)
Review and comments of the book The Creation of a Learning Society of the Nobel Prize Joseph Stiglitz.ResumenRevisión y comentarios del libro La Creación de una Sociedad del Aprendizaje del premio Nóbel Joseph Stiglitz.ResumoRevisão e comentários do livro A Criação de uma Sociedade de Aprendizagem do Prêmio Nobel Joseph Stiglitz.